Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Property Dan Real Estate - Alvin Valerie, Elizabeth Sugiarto Dermawan (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence about the determinants of firm value in property and real estate companies listed on Indonesia Stock Exchange 2015-2017. The determinants of this research are financial leverage, firm size, profitability and liquidity. The research method used was purposive sampling with a total sample of 46 companies listed on the Indonesia Stock Exchange (IDX). Data is obtained from financial statements taken from www.idx.co.id. Hypotheses were tested using multiple linear regression because there are 4 independent variables tested in this research. The result of this research showed that financial leverage and profitability has positive effect on firm value, while firm size and liquidity have no significant effect on firm value